PEMENUHAN STANDAR KUALITAS AIR SUNGAI DI INDONESIA SESUAI PP No. 82/ 2001 - Dewi Ratnaningsih (Jurnal Ecolab, 2008)
The aim of this report is in order to perform the conformity of environmental quality standards for river water inIndonesia and also in each regional area based on the Indonesian government regulation No. 82/ 2001. The riverwater quality data were collected from 2007. For additional information, data of 2003 to 2006 were also used.Data were derive from all over Indonesia including 33 rivers of 30 provinces in each regional area were also calculated.The result indicated that river water quality in Indonesia were already contaminated by human activities.Several environmental parameter such as DO, BOD, COD, phenol, fecal coli, and total coliform are still not beingmet according to The Water Quality Criteria Class I of Government Regulation No. 82/ 2001 at 50% of the totaldata. Regarding to the regional area, the conformity of water quality standards of DO, BOD, COD, and phenolcoud not also meet the requirements of Water Quality Criteria Class I more than 50% in each of five (5) regionalareas of Sumatera, Jawa, Kalimantan, Sumapapua and Balinusra. In high populated area such as Jawa RegionalArea, fecal coli and total coliform also becomes a serious river water quality problem. Besides of those parametersTSS and T-P also relatively give important contributions to river water pollution. Regarding to these results it isnecessary to do an effort in order to reduce water pollution by controlling the source of pollution parameters suchas controlling of the organic wastes from industrial and domestic wastes, agricultural run offs, human and animalhusbandry wastes and also the erosion in order to enhance and get better condition of river water quality in Indonesia.